Preliminary study of shark microbiota at a unique mix-species shark aggregation site, in the Eastern Mediterranean Sea - Bregman, Goni; Lalzar, Maya; Livne, Leigh; Bigal, Eyal; Zemah-Shamir, Ziv; Morick, Danny; Tchernov, Dan; Scheinin, Aviad; Meron, Dalit (Frontiers in Microbiology, 2023)
Sharks, as apex predators, play an essential ecological role in shaping the marine food web and maintaining healthy and balanced marine ecosystems. Despite their status, sharks are sensitive to environmental changes and anthropogenic pressure, and demonstrate a clear and rapid response. This designates them a “keystone” or "sentinel" group that may describe the structure and function of the ecosystem. As a meta-organism, sharks offer selective niches (organs) for microbes that can provide benefits for their hosts. However, changes in the microbiota (due to physiological or environmental changes) can turn the symbiosis into a dysbiosis and may affect the physiology, immunity and ecology of the host. Although the importance of sharks within the ecosystem is well known, relatively few studies have focused on the microbiome aspect, especially with long-term sampling. Our study was conducted at a site of coastal development in Israel where a seasonal aggregation (November-May) of the two same genus shark species, the dusky (Carcharhinus obscurus) and sandbar (Carcharhinus plumbeus) segregate by sex (females and males, respectively). In order to characterize the bacterial profile and examine the physiological and ecological aspects, microbiome samples were collected from different organs (gills, skin, and cloaca) from both shark species over three distinct seasons (2019, 2020 and 2021). The bacterial composition was significantly different between the sharks and the surrounding seawater and between the shark species. Additionally, differences were apparent between all the organs and the seawater, and between the skin and gills. The most dominant groups for both shark species were Flavobacteriaceae, Moraxellaceae, and Rhodobacteraceae. However, specific microbial biomarkers were also identified for each shark. An unexpected difference in the microbiome profile and diversity between the 2019-2020 and 2021 sampling seasons, revealed an increase in the potential pathogen Streptococcus. The fluctuations in the relative abundance of Streptococcus between the months of the third sampling season were also reflected in the seawater. Our study provides initial information on shark microbiome in the Eastern Mediterranean Sea. In addition, we demonstrated that these methods were also able to describe environmental episodes and the microbiome is a robust measure for long-term ecological research.